Publicidad inclusiva: La nueva apuesta de nike - Manjarres Garcia, Katerine Ivett (2019)
Currently, inclusive advertising is a tool used by marketing to attract customers or users through the identification or creation of an emotional bond, in the development of this project the advertising campaign designed by Nike “Just Do It ”, the same one that features quarterback Colin Kaepernick, who starred in a moment of protest in the history of the NFL when he kneeled to the ground while singing the national anthem of the United States, as a complaint against the wave of Racial discrimination that was being lived in 2017, Nike decided to take it as an example of overcoming and showing appreciation to Afro-descendant consumers, this campaign also joined other prominent athletes such as Serena Williams tennis player and Lebron James basketball player, in the campaign it shows images of disabled people seeking to achieve their dream in a country of opportunities and not violence ia, where inclusion allows to generate an environment of opportunities, despite adversities. It is important to take into account that inclusive advertising allows to generate a social criticism with the aim of attracting customers or loyalty by supporting the consumer, in addition to Nike there are other companies that have used inclusive advertising in their companies adopting another niche of the market that has not been exploited and looking for ways to create an identity of support and inclusion